2023
DOI: 10.1080/19490976.2023.2221098
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of hepatic growth hormone receptor (GHR) alters the mouse gut microbiota by affecting bile acid metabolism

Zichao Yu,
Yu Wang,
Fang Zhang
et al.

Abstract: Both growth hormone (GH) and gut microbiota play significant roles in diverse physiological processes, but the crosstalk between them is poorly understood. Despite the regulation of GH by gut microbiota, study on GH’s influence on gut microbiota is limited, especially on the impacts of tissue specific GH signaling and their feedback effects on the host. In this study, we profiled gut microbiota and metabolome in tissue-specific GHR knockout mice in the liver (LKO) and adipose tissue (AKO). We found that GHR di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Moreover, elevated BSH levels are associated with increased bile toxicity [47]. According to reports, Parasutterella [48], Odoribacter [49], Dubosiella [50], Family XIII AD3011 group [51], Christensenellaceae R7 group [52], Eubacterium coprostanoligenes group [53], and Alloprevotella [54] can also regulate BA metabolism through direct colonization or indirect action. In our Spearman's correlation analysis, we further confirmed that altered levels of BA metabolizing genera were the main cause of elevated fecal secondary BA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated BSH levels are associated with increased bile toxicity [47]. According to reports, Parasutterella [48], Odoribacter [49], Dubosiella [50], Family XIII AD3011 group [51], Christensenellaceae R7 group [52], Eubacterium coprostanoligenes group [53], and Alloprevotella [54] can also regulate BA metabolism through direct colonization or indirect action. In our Spearman's correlation analysis, we further confirmed that altered levels of BA metabolizing genera were the main cause of elevated fecal secondary BA levels.…”
Section: Discussionmentioning
confidence: 99%